Accounting information systems as a driver of financial performance: insights from Colombo’s apparel industry - Perera, M.S.D.; Shamila, L.M.A. (Journal of Multiperspectives on Accounting Literature, 2025)
Purpose: This study aims to examine the impact of Accounting Information Systems (AIS) on the financial performance of the apparel industry in the Colombo district, Sri Lanka, addressing the research gap regarding AIS application in this specific context. Methodology/approach: A quantitative research approach was employed using convenience sampling. Data were collected through a structured questionnaire from 265 respondents across eight leading apparel companies in the Colombo district. Descriptive statistics and regression analysis were used to assess the adoption level of AIS and its impact on financial performance. Findings: The study found a high level of AIS adoption and financial performance among the surveyed apparel companies. There is a significant strong positive relationship between AIS and financial performance. Regression analysis revealed that management support, record keeping performance, and accounting knowledge significantly influence financial performance, with an R-squared value of 0.70, indicating that AIS dimensions explain 70% of the variance in financial performance. Practical implications: The findings highlight the importance of optimizing AIS practices to improve financial outcomes in the apparel industry. Managers and stakeholders should prioritize management support, effective record keeping, and accounting knowledge to enhance organizational performance and competitiveness. Originality/value: This study contributes to the limited body of research on the role of AIS in the Sri Lankan apparel industry, providing empirical evidence of the system’s significant impact on financial performance and offering practical insights for industry stakeholders.